(untitled) (Anclajes, 2021)
In a game of approximations and evocations, Noé Jitrik invites us to explore the mutual interweaving of the political, the literary, and the psychoanalytic as dimensions that permeate his philosophy of writing. The latter, whose manifestation is transformed in its insinuation, houses the multiple forces of the act of reading, and then plots its forms and gestures. In doing so, we observe the sediments and possibilities for a way of thinking that rejects the mere mechanical application of discourses. At the same time, it gives rise to a language that ties together struggle and otherness in the act of writing. Therefore, it presents a form of resistance against silence as a blank space, and against the act of silencing produced by hegemonic epistemologies. In this context, there emerge in the act of writing other dimensions of failure in relation to the attempt to capture meaning, fill gaps or eliminate forgetfulness. These other sides of writing outline a game between memory and forgetting, between presence and absence, and between impossibility and negativity, which point to how the whistles of silence prowl while writing flourishes in its philosophical mischief.